The experience of bilateral lung retransplantation after prolonged extracorporeal oxygenation - E. A. Tarabrin; M. Sh. Khubutiya; A. S. Guseva; E. A. Ermakova; E. I. Pervakova; S. V. Zhuravel; A. M. Gasanov; V. G. Kotandzhyan; N. A. Karchevskaya; T. E. Kallagov; I. U. Ibavov; M. S. Kevorkova; et al. (Трансплантология (Москва))
Background. Transplantation is the only effective method of helping patients with irreversible damage of the lung function when the possibilities of other treatment methods have been exhausted. At the same time, a chronic graft rejection is the main cause of the loss of the donor organ function in the long-term period, developing in more than 50% of patients within 5 years after surgery. Given irreversible lung damage with loss of lung functions, the only effective treatment method for this patient population is retransplantation, which is associated with high risks of complications and a long rehabilitation of the patient in the postoperative period.Objective. Demonstration of the first Russian experience of bilateral lung retransplantation in a patient after a longterm extracorporeal oxygenation.Results. The article presents the description of the first experience of bilateral lung retransplantation in Russia performed in a patient with a chronic rejection 4.5 years after the primary transplantation performed for end-stage lung lesions in non-langerhans cell histiocytosis. In the 96-day period of waiting for a donor organ, the patient's gas-exchange lung function was compensated by using veno-venous extracorporeal membrane oxygenation.Conclusions. Retransplantation is an effective method of treatment for patients with irreversibly damaged lung function, but still remains an operation associated with high risks of complications and unfavorable outcome.